Determinants of maternal and reproductive health service utilization among plain land tribal women in Bangladesh: A mixed-methods study - Md Ruhul Amin (Indonesian Journal of Health Services, 2026)
Background: Maternal and reproductive health disparities persist among indigenous populations in Bangladesh despite national progress in reducing maternal mortality. Plain land tribal women remain particularly vulnerable due to socioeconomic marginalization, geographic isolation, and cultural barriers that limit equitable access to essential healthcare services. Objective: This study aimed to examine the barriers, utilization patterns, and determinants of maternal and reproductive health service use among plain land tribal women in northern Bangladesh. Methods: A mixed-methods design was employed in four northern districts with substantial tribal populations. The quantitative phase involved a cross-sectional survey of 200 tribal women of reproductive age who had experienced pregnancy within the previous three years. Data were analyzed using descriptive statistics, correlation analysis, and multivariate regression modeling. The qualitative phase included in-depth interviews and focus group discussions with tribal women, community leaders, and healthcare providers. Thematic analysis was conducted to explore sociocultural and institutional factors influencing service utilization. Results: Although awareness of antenatal care was relatively high (77.5%), only 44% of women reported institutional delivery and 19% completed more than four antenatal visits. Education level, household income, proximity to health facilities, and decision-making autonomy were significant predictors of maternal healthcare utilization. Cultural preferences for traditional birth practices, financial constraints, and geographic barriers were negatively associated with service uptake. Contact with community health workers significantly improved antenatal care awareness, while respectful provider behavior positively influenced service satisfaction. Conclusion: Maternal and reproductive health service utilization among plain land tribal women is shaped by intersecting structural, socioeconomic, and cultural determinants. Addressing disparities requires integrated strategies that combine educational empowerment, economic support, geographic outreach, and culturally responsive maternity care to ensure equitable healthcare access for marginalized indigenous populations.